THE EFFECT OF 1,25-DIHYDROXYVITAMIN-D3 ON LYMPHOCYTE-TRANSFORMATION IN PATIENTS WITH CHRONIC-RENAL-FAILURE - (:unkn) unknown (JAPAN SOC INTERNAL MEDICINE, 1995)
The changes in mitogen-induced lymphocyte response occurring in nine patients undergoing chronic hemodialysis and treated with 1,25 dihydroxyvitamin D-3 (0.5 mu g/day) were investigated, Prior to treatment the stimulation indices (SI) in patients with 15.4+/-4.2 for phytohemagglutinin (PHA) and 7.2+/-0.7 for conconavalin A (Con A), In the controls, stimulation indices were 44.4+/-13.5 and 20.2+/-5.3 for PHA and Con A, respectively, Following treatment, the stimulation indices increased to 36.9+/-6.2 for PHA (p<0.05) and 18.6+/-3.9 for Con A (p>0.05) indicating the beneficial effect of oral 1,25 dihydroxyvitamin Dg treatment on lymphocyte function in patients with chronic renal failure.
Keywords: VITAMIN D; LYMPHOCYTE FUNCTION; CONCONAVALIN A; PHYTOHEMAGGLUTININ